2013
DOI: 10.1161/hypertensionaha.113.01613
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–Independent Angiotensin-(1–7) Formation in Rat Hippocampus

Abstract: The involvement and relevance of the renin–angiotensin system have been established clearly in cardiovascular diseases, and renin–angiotensin system involvement has also been investigated extensively in the central nervous system. Angiotensin II acts classically by binding to the AT 1 and AT 2 receptors. However, other pathways within the renin–angiotensin system have been described more recently, such as one in which angiotensin-(1–7) (Ang-(1–7)) binds to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
(38 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, these investigators reported higher expression of this peptidase and the Mas receptor in a rat model of temporal lobe epilepsy suggesting a possible role of the Ang-(1-7)-Mas axis in this central pathology (28). Indeed, the study supports earlier reports of the direct processing of Ang I to Ang-(1-7) by thimet oligopeptidase in vascular smooth muscle cells and a rat hindlimb perfusion system (29,30).…”
Section: Sources Of Angiotensin-(1-7)supporting
confidence: 83%
“…Interestingly, these investigators reported higher expression of this peptidase and the Mas receptor in a rat model of temporal lobe epilepsy suggesting a possible role of the Ang-(1-7)-Mas axis in this central pathology (28). Indeed, the study supports earlier reports of the direct processing of Ang I to Ang-(1-7) by thimet oligopeptidase in vascular smooth muscle cells and a rat hindlimb perfusion system (29,30).…”
Section: Sources Of Angiotensin-(1-7)supporting
confidence: 83%
“…8 Furthermore, the level of Ang-(1–7) was detected from the hippocampus using high-performance liquid chromatography assay and increased during the acute and silent phases of pilocarpine-induced epilepsy. 12 Pereira et al 13 show that Ang-(1–7) is the main metabolite of Ang I in rat hippocampi. These results also suggest that the ACE2/Ang-(1–7)/Mas receptor axis in the brain is essential for cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in Mas Ϫ/Ϫ mice, ANG-(1-7) concentrations are increased in the whole hippocampus, as well as in the CA1 area, suggesting the need for a functional ANG-(1-7)/MAS axis for normal ORM processing (299). Interestingly, it has been reported that in this brain region ANG-(1-7) can be formed independent of ANG II processing (417). Despite this evidence, the role of ANG-(1-7)/MAS axis in limbic-dependent memories remains poorly understood.…”
Section: Other Angiotensin-(1-7) Effects In the Brainmentioning
confidence: 95%